COVID-19 in Nigeria: Implications for Management of Related Co-morbidities, Prevalent Public Health Challenges, and Future Epidemic Preparedness - Toyin Togun; Bolanle A. Ola; Esin Nkereuwem; Eniyou C. Oriero; Uduak Okomo; Muhammed O. Afolabi (The Proceedings of the Nigerian Academy of Science, 2020)
The Coronavirus Disease-2019 (COVID-19) pandemic is now well-established in Africa with cases reported from all countries on the continent. Despite the significant progress that has been made in the response to the pandemic in Nigeria, relative to the period of Ebola epidemic, the currently reported number of COVID-19 cases are likely under-estimates of the true number of cases. This is attributable to restricted testing capacity due to limited technical, infrastructural, financial, and logistical capacity to rapidly scale-up testing. In this article, we explore the impact of the COVID-19 pandemic on management of related co-morbidities and the major prevalent public health challenges, including mental health, in Nigeria, Africa’s most populous country. We also discuss the most current knowledge about candidate vaccines for the control of the novel coronavirus (SARS-CoV-2) strain. The interactions between COVID-19 and the endemic public health challenges in Nigeria further highlight the linkage between infectious diseases and poverty, and emphasise the need for a sustained increase in investments in the general public health system that is geared toward achieving Universal Health Coverage in Nigeria.